99.0k views
1 vote
To prove :One plus cot square theta into tan theta by sec square theta = cot theta

User Paulgv
by
5.2k points

1 Answer

2 votes

we are given


((1+cot^2(\theta))*tan(\theta))/(sec^2(\theta)) =cot(\theta)

We will simplify left side and make it equal to right side

Left side:


((1+cot^2(\theta))*tan(\theta))/(sec^2(\theta))

we can use trigonometric identity


1+cot^2(\theta)=csc^2(\theta)

we can replace it


((csc^2(\theta))*tan(\theta))/(sec^2(\theta))

we know that

csc=1/sin and sec=1/cos

so, we can replace it

and we get


(cos^2(\theta)tan(\theta))/(sin^2(\theta))

now, we know that

tan =sin/cos


(cos^2(\theta)*sin(\theta))/(sin^2(\theta)*cos(\theta))

we can simplify it

and we get


(cos(\theta))/(sin(\theta))

we can also write it as


=cot(\theta)

Right Side:


cot(\theta)

we can see that

left side = right side

so,


((1+cot^2(\theta))*tan(\theta))/(sec^2(\theta)) =cot(\theta)......Answer

User Adam Kotwasinski
by
6.2k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.